The demand for imports and exports in Africa: A survey - Michael Olabisi; W. Charles Sawyer (Journal of African Trade, 2020)
To drive economic development, it is important for policy makers to have a good understanding of the linkages between imports, exports, and the rest of the economy. This is particularly true for Africa. The continent depends on exports of commodities to finance imports of manufactured goods for consumption and investment purposes. The importance of trade to African economies is underscored by one fact: the region has one of the highest ratios of imports and exports to gross domestic product. In this paper, we survey the literature on import and export demand elasticities and present a broad set of estimates for the countries of Africa. These estimates collected in our survey can support both academic research and policy making on the continent. They also provide a road map for future research on the determinants of trade flows on the continent. The results reveal large gaps in our understanding of the determinants of trade flows in the region-those gaps serve as pointers for future research.
Keywords: 330; African trade; export demand elasticity; import demand elasticity; survey; Außenhandelselastizität; Schätzung; Bibliometrie; Afrika